2D Graphene‐Based Macroscopic Assemblies for Micro‐Supercapacitors. Issue 6 (2nd March 2020) - Gao, Chang; Chen, Kaiyue; Wang, Ying; Zhao, Yang; Qu, Liangti
Abstract: Rapid development of portable and wearable electronic devices has triggered increased research interest in small‐scale power sources, especially in micro‐supercapacitors (MSCs) because of their high power densities, long service life, and ability to be charged and discharged quickly. Graphene, an ideal two‐dimensional energy‐storage electrode material with good conductivity, high quantum capacitance, and large specific surface area, can be used as a building block for MSCs with multi‐dimensional architectures. Considerable efforts have been devoted to constructing structures with different dimensions for advanced graphene‐based MSCs (GMSCS). In this Review, we summarize the recent progress of graphene‐based macroscopic assemblies in MSCs, including 1D fiber GMSCs, 2D planar GMSCs; and 3D in‐plane or stacked GMSCs, and discuss the relationship between the structures and applications of the devices. In addition, future prospects and challenges in the MSCs are also discussed. Abstract : It′s in the shape : The Review discusses the latest progress achieved for graphene‐based micro‐supercapacitors. In addition, the three possible dimensionalities of the prepared materials are discussed, including 1D fibers, 2D planar shape, and 3D in‐plane or stacked shapes. Some challenges and prospects are also addressed required to achieve potential applications in a wide range of fields.